Interspecific interactions between Uroplata girardi (Coleoptera: Chrysomelidae) and Ophiomyia camarae (Diptera: Agromyzidae), and their impact on a shared host Lantana camara (Verbenaceae) in South Africa - mishapril@yahoo.com (University of Pretoria, 2013)
Dissertation (MSc (Entomology))--University of Pretoria, 2009.